Dėl u kamieno būdvardžių ir jų abstraktų kirčiavimo raidos - Lazauskaitė, Vilija (Baltistica, 1998)
ON THE EVOLUTION OF THE ACCENTUATION OF u-STEM ADJECTIVES AND ABSTRACT NOUNSOn the basis of the data from Daukša’s works presented by Skardžius the article considers the causes of the oxytonic process in barytonic u-stem adjectives, cf. daĩlus -> dailùs, skáistus -> skaistùs.Of more than two thirds of the old accentuation cases found in Daukša’s works there remained but a few in Kuršaitis’ dictionary and dialects. The barytonic nature of the said adjectives can be recognized by their neuter forms stressed on the root, which are quite plentiful in Kuršaitis’ dictionary and are still in use in present-day dialects, cf. baĩsu, vė̃su and others.Stress on the root in u-stem adjectives is partly determined by the variation between u- and o-stem adjectives in East Lithuanian subdialects, cf. rū́gštus and rū́gštas. This shows that u-stem adjectives could be related to o-stem forms as well. When the said forms changed into the u-stem, the neuter forms of adjectives may have retained the old stress longer, e. g. pìgas, -à, pìga -> pìgus, -ì, pìgu ->pigùs, -ì, pìgu and pigù.In Daukša’s works not only u-stem adjectives and their forms receive stress on the root, but also derivatives with the suffix -umas which usually preserve the stress of the basic word, e.g. brángumas: brángus, kañtrumas : kañtrus and others, with the exception of baisùmas, cf. baĩsus, teisùmas, cf. teĩsus. Both latter cases show that in Daukša’s times there may have been a tendency towards suffixal accentuation in nouns. After de Saussure and Fortunatov’s Law the stressed suffix -umas could have influenced the formation of the old accentuation in u-stem adjectives with stress on the ending, cf.*méilumas          →       meilùmas        ↑                                 ↓                   < ́ / ˜>*méilus, méilų   →     meĩlų, meilùs
Keywords: acentology; lithuanian; adjective